Pengaruh Etika Profesi, Budaya Organisasi, Gaya Kepemimpinan Dan Kompetensi Terhadap Kinerja Auditor Pada Kantor Akuntan Publik Padang - Kiki Patmala Daulay; Indrayeni (CV. ITTC INDONESIA, 2024)
This research aims to determine the influence of Professional Ethics, Organizational Culture, Leadership Style and Competency on Auditor Performance at the Padang Public Accounting Firm. The method used in this research is a quantitative method. With a total sample of 31 respondents taken using simple random sampling techniques. The model used in this research is a regression model which is processed with the statistical data processing application SPSS version 25. The results of the research show that Professional Ethics has no influence on Auditor Performance. Organizational culture has a negative and significant effect on auditor performance. Leadership Style has a positive and significant effect on Auditor Performance and Competency has a positive and significant effect on Auditor Performance. It is hoped that this research contribution can provide information as a supporting basis and contribute ideas to Public Accounting Firms in Padang City in order to maintain and maintain the image of Public Accounting Firms and improve their performance in carrying out their professional duties.